Significance of screening sensitive methylation sites using whole-genome sequencing in early diagnosis of non-small cell lung cancer - Zhang, Yu; Lu, Ning; Pu, Shunchang; Mu, Kui (Cellular and Molecular Biology, 2022)
The current study aimed to screen the sensitive methylation sites of non-small cell lung cancer by whole-genome sequencing and construct an early warning system for lung cancer. For this purpose, from June 2017 to December 2020, fresh NSCLC tissues and paired adjacent NSCLC tissues from 45 patients were collected. DNA and total RNA were extracted from non-small cell lung cancer (NSCLC) and paired non-cancerous lung tissues. The DNA library combined with a biotinylated probe was collected by Dynabeads m270 streptavidin beads. The concentration of the final library was determined by qubit dsDNA HS assay. Quantitative analysis of DMR methylation in 45 paired tumor and normal lung tissues was performed. RT qPCR and Western blot were used to verify the mRNA expression of candidate genes. Results showed that the methylation rate of CpG 7 in stxbp6 in stage III NSCLC was higher than that in stage I and early-stage II NSCLC; The methylation rates of cpg1 and 38-39 units in fzd10 were higher in stage I NSCLC than in stage II and III NSCLC; The methylation rates of CpG 6 in stxbp6 and CpG 4 and 20-21 in bcl6b in patients with tumor diameter > 3cm were higher than those in patients with tumor diameter < 3cm; Methylation of CpG unit 3 in stxbp6 is associated with age. Stxbp6, bcl6b, fzd10 and hspb6 mRNA expression were down-regulated in patients under 45 years old. The methylation rates of CpG 7 in stxbp6, CPG 6 in stxbp6 and CpG 4 and 20-21 in bcl6b were negatively correlated with the survival time of patients; The methylation rates of CpG 1 and 38-39 units in fzd10 were positively correlated with survival time (P<0.05). It was concluded that the methylation rates of CpG 7 in stxbp6, CPG 6 in stxbp6 and CpG 4 and 20-21 in bcl6b are valuable for early diagnosis.